ANALYSIS OF LOGISTICS PERFORMANCE OF EU 27 COUNTRIES WITH LOPCOW AND EDAS METHODS (Third Sector Social Economic Review, 2025)
In this study, we conducted a comprehensive analysis of the data from the 2007, 2010, 2012, 2014, 2016, 2018 and 2023 Logistics Performance Index (LPI) report announced by the World Bank (WB) of 27 countries in the European Union (EU) of the logistics sector in the world. We used Multi-Criteria Decision Making (MCDM) methods to measure the performance of countries, with infrastructure, customs services, logistics service quality and competence, international shipment, shipment tracking and timing as the LPI criteria. The weightings of the criteria were calculated separately for each year, and the LPI reports were announced using the precise LOPCOW (Logarithmic Percentage Change-driven Objective Weighting) method. The logistics performance of the countries was analyzed with the MCDM method EDAS (Evaluation Based on Distance from Average Solution) for each year in which the LPI reports were announced, and each year was evaluated within itself. Our literature research revealed that the methods used in this study have not been previously applied in the performance analysis of the logistics sector, making this study a pioneering contribution to the field. Our analysis revealed that Germany demonstrated the best performance, while Bulgaria showed the worst performance according to the average of all periods.
Keywords: Logistics; LPI; MCDM; LOPCOW; EDAS